Effects of rugby-specific concussion awareness program on collegiate rugby union players - Keita Suzuki; Satoshi Nagai; Masahiro Takemura (Journal of Physical Fitness and Sports Medicine)
This study assessed the effects of a rugby-specific concussion awareness program on improving the recognition of relevant symptoms and knowledge of concussion in male collegiate rugby union players. Thirty-one collegiate rugby union players from Japan were offered a concussion awareness program; they responded to a questionnaire assessing symptom recognition and knowledge of concussion three times (before, immediately after, and four weeks after the implementation of the program). Immediately after the program, the recognition score of suspected concussion symptoms was higher compared to before and four weeks later, when it was still higher than before the program, but not statistically significant. In addition, more players selected the correct answers about rugby-specific concussion topics after the program. Our findings suggest that while concussion awareness is expected to improve immediately, this effect was not maintained after four weeks. Therefore, concussion awareness opportunities should be scheduled regularly, such as at the start of each season, before the beginning of competition season, and when new players join the team.